The Relationship between Leadership Effectiveness of School Principals and Teachers Performance of Junior High Schools - Paquita, Natasya Paquita; Wiyono, Bambang Budi; Zulkarnain, Wildan (Universitas Negeri Malang, 2021)
The leadership effectiveness of school principals and teacher performance are two variables that determine school progress. With leadership effectiveness of the school principal and good teacher’s performance will improve school performance. The question is whether the two variables are related. Therefore, this research aimed at determining the level of leadership effectiveness of the school principal, describing the level of teacher’s performance, and determining the coefficient of the relationship between the leadership effectiveness of the school principal and teacher performance. This research was conducted in State Junior High Schools in Lowokwaru District, Malang City, using a simple correlation model quantitative research approach. The research sample was taken from 156 teachers with a proportional random sampling technique. Data collection techniques in this research employ a questionnaire and are processed with statistical data analysis techniques, descriptions, and Pearson Product moment correlation. The results of this research show that the level of the leadership effectiveness of the school principals is in the high category, while the teacher’s performance level is in the medium category. There is a significant positive relationship between the leadership effectiveness of the school principals and teacher’s performance. Based on these findings, to improve teachers’ performance, it needs to improve the leadership effectiveness of the school principals.